Hydrolytically Stable Ionic Fluorogels for High‐Performance Remediation of Per‐ and Polyfluoroalkyl Substances (PFAS) from Natural Water. (2nd September 2022) - Manning, Irene M.; Guan Pin Chew, Nick; Macdonald, Haley P.; Miller, Kelsey E.; Strynar, Mark J.; Coronell, Orlando; Leibfarth, Frank A.
Abstract: PFAS are known bioaccumulative and persistent chemicals which pollute natural waters globally. There exists a lack of granular sorbents to efficiently remove both legacy and emerging PFAS at environmentally relevant concentrations. Herein, we report a class of polymer networks with a synergistic combination of ionic and fluorous components that serve as granular materials for the removal of anionic PFAS from water. A library of Ionic Fluorogels (IFs) with systematic variation in charge density and polymer network architecture was synthesized from hydrolytically stable fluorous building blocks. The IFs were demonstrated as effective sorbents for the removal of 21 legacy and emerging PFAS from a natural water and were regenerable over multiple cycles of reuse. Comparison of one IF to a commercial ion exchange resin in mini‐rapid small‐scale column tests demonstrated superior performance for the removal of short‐chain PFAS from natural water under operationally relevant conditions. Abstract : The design and synthesis of a library of ion exchange resins that are selective for PFAS removal from real water enabled the evaluation of structure–property relationships of the chemically stable polymer networks with high PFAS affinity. The granular Ionic Fluorogel resin is a potent PFAS remediation sorbent and demonstrated excellent performance in translationally relevant flow‐through packed bed columns using natural water.